A new shortening rate across the Dushanzi anticline in the northern Tian Shan Mountains, china from lidar data and a seismic reflection profile. (1st September 2018) - Su, Peng; He, Honglin; Wei, Zhanyu; Lu, Renqi; Shi, Feng; Sun, Haoyue; Tan, Xibin; Hao, Haijian
Graphical abstract: Highlights: The subsurface structure of the Dushanzi anticline is constrained using a new high-quality seismic reflection profile. Folding and faulting shortening rates across the Dushanzi anticline are quantified. The average coseismic displacement and the average recurrence interval of the Dushanzi frontal fault are calculated. Abstract: In the northern foreland basin of the Tian Shan Mountains, strata have been intensively deformed as a result of the ongoing Cenozoic Indian-Eurasian collision. The Dushanzi anticline lies in the northernmost deformation belt of the Tian Shan Mountains. Understanding the shortening rate and paleoseismicity of the Dushanzi anticline is important for both understanding the propagation of the thrust front of the Tian Shan Mountains and for assessing seismic hazards in this highly populated area. Here we integrate lidar-derived topographic data, a high-quality seismic reflection profile, and field observations across the Dushanzi anticline to resolve the Holocene deformation history of the anticline. A reconstructed longitudinal profile along the Kuitun River that flows across the Dushanzi anticline demonstrates a Holocene history of both folding and faulting. The total shortening from faulting is 4.4 ± 0.1 m, while the shortening accommodated by folding is 12.6 ± 1.1 m since 7.5–10 ka B.P. A total of 17.0 ± 1.1 m of shortening has occurred across the Dushanzi anticline in the Holocene at a rate of 2.0 ± 0.2 mm/a. This shortening represents up to 18% of the  >11 mm/a total shortening rate across the entire eastern Tian Shan Mountains at this longitude. The Holocene shortening rate of the Dushanzi anticline is ∼6 times greater than its long-term average shortening rate (0.3 ± 0.1 mm/a) since 4.8 Ma. Furthermore, we analyzed a displaced terrace sequence at a site along the Dushanzi frontal fault and found that the average coseismic dip-slip displacement is 2.5 ± 0.1 m, with an average recurrence interval of 2.8 ± 0.3 ka.